Urban Growth and Informal Settlements: Understanding the Evolution of Squatter Communities in Kathmandu Valley - Pyakurel, Nava Raj; Shrestha, Diwat Kumar (NPRC Journal of Multidisciplinary Research, 2025)
Kathmandu Valley, Nepal’s urban core, has witnessed unprecedented population growth and spatial expansion over the past five decades, resulting in the proliferation of informal or squatter settlements along riverbanks and peri-urban fringes. This study grounded entirely on secondary data sources census statistics, published reports, academic literature, spatial analyses, and institutional records examines the dynamics of urban growth and the evolution of informal settlements in the Valley. Through a comprehensive review and synthesis of existing research, the article analyzes the interconnections between demographic pressures, land-market transformations, policy gaps, and the socio-economic conditions of squatter communities. The findings reveal that informal settlements are not merely manifestations of poverty, but rather products of structural urban inequities, weak land governance, and inadequate housing policies. Environmental degradation, tenure insecurity, and limited access to services further exacerbate social vulnerability. The study identifies critical knowledge gaps in longitudinal monitoring, urban land management, and integrated planning frameworks. Policy discussions emphasize the need for inclusive urban strategies that balance environmental sustainability, affordable housing, and social justice. This review contributes to the understanding of urban informality in Nepal by consolidating fragmented evidence into a coherent framework for future research and policy reform.